2019
DOI: 10.1186/s13063-019-3866-6
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis plan for the Dex-CSDH trial: a randomised, double-blind, placebo-controlled trial of a 2-week course of dexamethasone for adult patients with a symptomatic chronic subdural haematoma

Abstract: BackgroundThe incidence of chronic subdural haematoma (CSDH) is increasing. Although surgery remains the mainstay of management for symptomatic patients, uncertainty remains regarding the role of steroids. Hence, the Dex-CSDH trial was launched in the UK in 2015 aiming to determine whether, compared to placebo, dexamethasone can improve the 6-month functional outcome of patients with symptomatic CSDH by reducing the rate of surgical intervention and recurrence rate.Methods and designDex-CSDH is a multi-centre,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Postoperative recurrence of subdural hematoma was a tertiary outcome that was defined as a symptomatic recurrence leading to reoperation of a previously evacuated ipsilateral chronic subdural hematoma. 19 Adverse events of special interest included hyperglycemia leading to treatment or discontinuation of the trial regimen, new-onset diabetes, hyperosmolar hyperglycemic state, new-onset psychosis, peptic ulceration or gastrointestinal bleeding, and other upper gastrointestinal side effects. 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative recurrence of subdural hematoma was a tertiary outcome that was defined as a symptomatic recurrence leading to reoperation of a previously evacuated ipsilateral chronic subdural hematoma. 19 Adverse events of special interest included hyperglycemia leading to treatment or discontinuation of the trial regimen, new-onset diabetes, hyperosmolar hyperglycemic state, new-onset psychosis, peptic ulceration or gastrointestinal bleeding, and other upper gastrointestinal side effects. 10…”
Section: Discussionmentioning
confidence: 99%
“…The independent data monitoring and ethics committee recommended that recruitment should continue to the original target sample size of 750 patients. The analysis was conducted according to a statistical analysis plan, 19 which was agreed on without reference to the unblinded data (see the protocol). No alpha-spending adjustment was required as a result of the 100-patient pilot trial, because this pilot phase was designed solely to determine the operational feasibility of continuing the trial.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a small recent randomized control trial comparing corticosteroids to placebo among patients with cSDH found that steroids may decrease the risk of requiring surgical evacuation (38). Larger randomized clinical trials are underway to investigate this therapy (39)(40)(41).…”
Section: Demographic Characteristics and Treatmentmentioning
confidence: 99%
“…Clearly a rather robust inflammatory response of the brain to the initial SDH is elicited and persists ( 7 , 12 ). Recent trials have been directed at attenuating this response with dexamethasone or atorvastatin ( 19 , 20 , 37 ). There has also been much recent interest in middle meningeal artery (MMA) embolization for the treatment of cSDH.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for cSDH include surgery (15)(16)(17), observation and medications such as dexamethasone (12,(18)(19)(20) and endovascular obliteration of the meningeal artery (21)(22)(23)(24)(25). There have been numerous studies examining the different procedures.…”
Section: Figure 2 |mentioning
confidence: 99%